مناخ الاستثمار في الجزائر المعيقات واستشراف البدائل - جنان, أحمد; بن حسان, حكيم; بن فضة, ويسام (جامعة الوادي - University of Eloued, 2021)
نهدف من خلال هذه الورقة البحثية إلى محاولة توضيح مدى مساهمة السياسة المالية المنتهجة في الدول النامية في توفير مناخ استثماري جاذب للاستثمار الأجنبي المباشر، مع التركيز على حالة الجزائر. ولقد تم الاعتماد في هذه الدراسة على المنهج الوصفي التحليلي لتلائمه مع طبيعة الموضوع مع تعزيز بحثنا بالإحصائيات والبيانات الضرورية. توصلت هذه الدراسة إلى أنه منذ تبني الجزائر الانتقال لاقتصاد السوق، شهدت السياسة المالية المطبقة من طرف الدولة تطورات مستمرة بهدف تحسين المناخ الاستثماري فيها. ورغم كل الجهود المبذولة فلا يزال هذا المناخ يوصف أنه غير مؤهل تأهيلا كافيا لاستقطاب الاستثمار الأجنبي، رغم تحقيق هذه السياسة بعض النتائج الإيجابية على المستوى المؤشرات الاقتصادية الكبرى. Through this paper, we seek to clarify the extent to which the financial policy adopted in developing countries contributes to the creation of an attractive investment climate for foreign direct investment, focusing on the case of Algeria. In this study, we have relied on the descriptive and analytical approach adapted to the nature of the subject while enriching our research with the necessary statistics and data. This study revealed that since Algeria's transition to a market economy, the financial policy applied by the State has undergone continuous changes with a view to improving the investment climate within the country. Despite all the efforts made, this climate is still described as insufficiently qualified to attract foreign investment, despite the fact that this policy is achieving positive results in terms of the main economic indicators.
Algeria's investment climate: brakes and explore alternatives
مقال
Keywords: السياسة المالية ; الاستثمار الأجنبي المباشر ; الجزائر